PENGARUH KEPEMIMPINAN STRATEGIS TERHADAP MODAL INTELEKTUAL - masmarulan, masmarulan; Muliati, Muliati (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2023)
This research aims to determine the influence of Strategic Leadership on Intellectual Capital on PT employees. Cement Tonasa Pangkep. The associative method was used in this research. The data collection method used was a questionnaire which was measured using a Liker scale, with sampling using the Solvin formula so that the sample totaled 322 employeess. The data analysis technique used the t test. The findings show that strategic leadership has a significant positive influence on employee intellectual capital.